Competence Improvement of School Libraries in Realizing Adaptive Service Innovation - Muhammad Erdiansyah Cholid Anjali; Zeni Istiqomah (Record and Library Journal, 2023)
Background of the study: Librarians are required to adapt to the surrounding environment in all eras. During the post-Covid-19 pandemic period, returning the spirit of offline learning by providing the right information resources for users at the school level is necessary. Improving the competence of librarians in managing the library is one of the keys. Purpose: This study aims to analyze how librarians adaptively improve their competency in the post-Covid-19 pandemic. Method: This research uses a qualitative approach and case study method. Data collection techniques were using observation, interviews, and documentation analysis. The validity of the data was tested using the source triangulation technique. Data are presented by reducing data, presenting data, and drawing conclusions. Findings: The librarian profession is a profession with competencies that develop adaptively. Improving the competence of school librarians in the post-pandemic period includes general competencies and core competencies. General competencies include operating computers, compiling work programs, and compiling reports. Improvement of core competencies includes a selection of library materials, acquisition of information sources, cataloging capabilities, maintenance of library materials, improvement of circulation services, reference services, information retrieval, library promotion capabilities, literacy, use of IT in libraries, as well as enhancement of specific competencies. Competency enhancement is carried out in various ways: through training, technical guidance, knowledge sharing, seminars, and workshops held online, hybrid, and offline. As well as comparative studies in other libraries, both online and offline. Conclusion: Online self-development activities are still the prima donna for librarians at the school level because they save costs and time. In contrast, offline activities are still a factor in cost considerations.